The SWOT Analysis of Strengthening Character Education In Junior High School - Rachmat Satria; Elvia Baby Shahbana (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2020)
This study aims to describe the swot analysis of character education strengthening in junior high schools which includes (1) character education curriculum management, (2) results of swot analysis of character quality improvement, and (3) the principal's strategic plan for strengthening character education based on SWOT analysis. This research was conducted at SMPN 15 Malang using a qualitative approach with a case study research design. Data was collected through in-depth interviews and documentation studies. Analysis of the data obtained produces findings that are in accordance with the problems being faced by the school. The results of the study are (1) character education curriculum management applied in the preparation of learning schedules, lesson plans, syllabus; and scientific journals. The Character Education Strengthening Program was formed through four components including school inputs, processes, outputs and outcomes, (2) the results of the swot analysis found that schools conduct conditional evaluations and are not tied to instruments, then reported to the Office of Education, integrating Adiwiyata values in learning and exposing the results of school work, and (3) the principal's strategic plan for strengthening character education is to use an aggressive strategy, an opportunity utilization strategy, a survival strategy, and a diversification strategy. Steps for Strengthening Character Education in learning include determining the size of the short-term and long-term programs, setting program indicators, assessing program performance, comparing performance results, connecting programs, and analyzing performance errors, and taking corrective actions.